Factors influencing the capital structure of sharia construction and building companies - Ghazali Syamni, Said Musnadi,; Mitra Prasetyo5, Jumadil Saputra3, umt.edu.my Irfan4, (Opción, 2019)
This study aims to amine the effect of tangibility, non-debt taxshields, firm size, profitability, and receivables to the capital structureby using panel regression based on the Common Effect model, fixedeffect model and random effect model. The results of this studyshowed that there was a negative influence of tangibility and firm sizeon the capital structure. Research implication concludes that investorsshould be more careful choosing a company, to invest their capital by looking at reliability, non-debt tax shields, firm size, profitability, andreceivables to improve the expected capital structure.